Effect of Lavender Aromatherapy Combination with Respiratory Relaxation on Postpartum Maternal Anxiety in Infant Care - Tri Marlinawati, Iin; Dian Shofia Reny Setyanti; Zulhijriani (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
Introduction: Postpartum mothers often experience physical and psychological problems. The new role as a mother is a trigger for anxiety. Anxiety that is not resolved immediately will trigger other problems such as stress and depression, so efforts are needed to make the maternal mood better through the use of lavender aromatherapy and respiratory relaxation techniques. Objectives: This research aims to analyze the effect of the combination of levender aromatherapy with respiratory relaxation on postpartum maternal anxiety in infant care. Methods: This research is quantitative. The design of the quasy research was experimental with pre and post test without control group. The research was carried out on December 5 – 19, 2024. The research sample was primipara postpartum maternal at PMB L Sragen with 32 respondents. The sampling technique used nonprobability sampling with purposive sampling. The instrument used observation sheets, lavender aromatherapy, SOPs, and HARS questionnaires. Data analyzed using the Wilcoxon Test. Results: Respondents anxiety before and after used the lavender aromatherapy combination with respiratory relaxation had a median of 22 in the pre-test and 13.5 in the post-test. The result of the Wilcoxon Test gotten a p-value of 0.000 (<0.05), then H0 was rejected and Ha was accepted. Conclusions: The combination of lavender aromatherapy with respiratory relaxation has an effect on reducing postpartum maternal anxiety in infant care.